Suprachoroidal silicone oil migration following 27 gauge 3 ports pars plana vitrectomy – a rare complication and its management - Fiza Shaheen,; Sahar Fatima,; Hashim Ali Khan,; Muhammad Amer Awan, (Journal of the Pakistan Medical Association, 2023)
Suprachoroidal silicone oil migration is an unusual complication of small gauge 3 ports Pars plana vitrectomy (3PPV) system. Our objective is to report a retrospective, observational case of an intra-operative suprachoroidal silicone oil (SO) migration during 27 gauge 3PPV and its successful surgical management. A 49 years old type 2 male patient with diabetes presented to the ophthalmology outpatient department with reduced visual acuity in his right eye. He was diagnosed as having tractional retinal detachment involving macula. During combined phaco-vitrectomy following injection of SO, peripheral choroidal elevations were noted suggesting suprachoroidal SO migration. In an attempt to drain this intra-operatively nasal sclerotomy was enlarged. Post-operative B scan showed significant choroidal detachment for which patient was re-scheduled for surgery after 1 day. Three radial trans-scleral incisions (2 nasal and 1 temporal) for drainage were made at the site of maximum choroidal detachment. ---Continue